أنماط مهارة المحادثة وحاجات طلبة اللغة العربية الناطقين بغيرها في المرحلة الجامعيّة في تنمية مهارة المحادثة (ماليزيا ومملكة تايلاند أنموذجًا): The Needs Analysis of Speaking Skills Among Non-Native Arabic Language Students at The University Stage in Developing Conversational Skill (Malaysia and Thailand: Case Study) - Hasan, Yaakob; Mohd Hamidin, Norfaezah; Zaini, Abdul Razif; Asmimana, Kate; Hengpiya, Abdulhakam; M. Kaba, Abdulai (‘Abqari Journal, 2024)
Previous studies indicate that the proficiency of Arabic language learners in non-Arabic speaking regions of Southeast Asia, particularly in Malaysia and Thailand, is weak despite some of them having a good grasp of linguistic rules. The reason behind this is their limited practice and use of the Arabic language. On the other hand, the primary purpose of language is communication and interaction with others. From this perspective, it is important to train learners to use the language in a variety of contexts and situations, as well as in different conversation styles. A study was conducted using a questionnaire consisting of ten conversation skill patterns for 30 Arabic language students at the undergraduate level in the Islamic University of Selangor, Malaysia, and Prince of Songkla University, Thailand. In the Islamic University of Selangor, the study found that the learners' needs were met with the discussion pattern ranking first, followed by the description of pictures ranking second, and then the storytelling pattern ranking third. In Prince of Songkla University, the study revealed that learners' needs were met with the role-play pattern ranking first, followed by the question and answer pattern ranking second, and then the representation pattern ranking third. تشير الدراسات السابقة إلى أنّ مستوى دارسي اللغة العربية الناطقين بغيرها في جنوب شرق آسيا، وخاصة ماليزيا وتايلند ضعيف، على الرغم من تمكن بعضهم من قواعد اللغة؛ والسبب في ذلك هو قلة ممارستهم واستخدامهم اللغة العربية. ومن ناحية أخرى، فإنّ الغرض الأساسي للغة هو التواصل والتفاعل مع الآخرين، ومن هذا المنطلق، ينبغي علينا تدريب الدارسين على استخدام اللغة في مجموعة متنوعة من السياقات والمواقف، وفي أنماط مختلفة في مهارة المحادثة، وقد قامت الدراسة بإجراء استبيان مكون من عشرة أنماط لمهارة المحادثة لعدد 30 طالب وطالبة اللغة العربية في مرحلة البكالوريوس في الجامعة الإسلامية بسلانجور، ماليزيا وكذلك في جامعة الأمير سونكلا، تايلند، وفي الجامعة الإسلامية بسلانجور، توصلت الدراسة في معرفة حاجات الدارسين إلى أن نمط (المناقشة) حصل على الرتبة الأولى ثم يليه نمط (وصف الصور) حصل على الرتبة الثانية، ثم يليه نمط (قصّ الحكايات) حصل على الرتبة الثالثة. وفي جامعة الأمير سونكلا، توصلت الدراسة في معرفة حاجات الدارسين إلى أن نمط (لعب الأدوار) حصل على الرتبة الأولى ثم يليه نمط (السؤال والجواب) حصل على الرتبة الثانية، ثم يليه نمط (التمثيل) حصل على الرتبة الثالثة.